2015
DOI: 10.1111/pace.12624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steroid Elution on Electrical Performance and Tissue Responses in Quadripolar Left Ventricular Cardiac Vein Leads

Abstract: Introduction: The use of steroid elution (SE) electrode in a cardiac pacing lead is known to suppress myocardial inflammation to lower pacing thresholds (PTs (PACE 2015; 38:966-972) steroid elution, quadripolar left ventricular cardiac vein lead, pacing threshold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Our previous preclinical animal study showed that proximal SE pacing electrodes significantly reduced PCTs compared to non‐SE pacing electrodes on quadripolar LV leads . Further, histological examination showed that SE reduced the tissue capsules surrounding the leads at the electrodes . However, the effect of SE on the long‐term performance of quadripolar LV leads is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous preclinical animal study showed that proximal SE pacing electrodes significantly reduced PCTs compared to non‐SE pacing electrodes on quadripolar LV leads . Further, histological examination showed that SE reduced the tissue capsules surrounding the leads at the electrodes . However, the effect of SE on the long‐term performance of quadripolar LV leads is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid‐eluting (SE) pacing electrodes have demonstrated a clinical benefit in lowering and stabilizing PCT on the cardiac pacing electrodes by reducing inflammation at the electrode/myocardial tissue interface . Our previous preclinical study showed SE on all pacing electrodes of the Attain Performa quadripolar LV lead (Medtronic, Minneapolis, MN, USA) lowered PCT and reduced the tissue capsule thickness surrounding the lead in the cardiac vein . The primary results from a large prospective multicenter study of the Attain Performa quadripolar LV leads demonstrated a high implant success rate and a low complication rate with multiple lead shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An IS‐4 CRT device can have a maximum choice of 17 pacing vectors theoretically, greatly increasing the chance of finding a low left ventricular capture threshold, which may significantly prolong device longevity (Fig. A) …”
Section: Factors Affecting Device Longevitymentioning
confidence: 99%
“…8A). [56][57][58][59] 1 and φ 2 to boost the input voltage V in by approximately n times, where n is the number of diode/transistor-capacitor pairs in the cascade. Each diode detracts from the final output voltage V out (< nV in ) and causes some inevitable heat loss through its "forward bias" voltage V f .…”
Section: Quadripolar Left Ventricular Leads and Multiple Pacing Vectorsmentioning
confidence: 99%